2012
DOI: 10.3892/or.2012.1895
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nuclear NHERF1 in colorectal cancer progression

Abstract: Abstract. NHERF1 (Na + /H + exchanger regulatory factor 1) is expressed in the luminal membrane of many epithelia, and associated with proteins involved in tumor progression. Alterations of NHERF1 expression in different sites of metastatic colorectal cancer (mCRC) suggest a dynamic role of this protein in colon carcinogenesis. We focused on the observation of the altered expression of NHERF1 from non-neoplastic tissues to metastatic sites by immunohistochemistry. Moreover, we studied, by immunofluorescence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…Surprisingly, nuclear NHERF1 expression was noted in most samples, suggesting that nuclear NHERF1 expression represents an early marker of pre-morphological triggering of colorectal carcinogenesis.A positive direct correlation between membrane NHERF1 and EGFR expression was observed by their co-localization. The authors hypothesize that nuclear NHERF1 expression, present in the early stages of carcinogenesis and related with poor prognosis, might contribute to the onset of malignant phenotype [41]. Independently, Hayashi [22] and Mangia [41] envisage a potential role for NHERF1 as a marker in colorectal cancer.…”
Section: Hepatocellular Carcinoma and Colorectal Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Surprisingly, nuclear NHERF1 expression was noted in most samples, suggesting that nuclear NHERF1 expression represents an early marker of pre-morphological triggering of colorectal carcinogenesis.A positive direct correlation between membrane NHERF1 and EGFR expression was observed by their co-localization. The authors hypothesize that nuclear NHERF1 expression, present in the early stages of carcinogenesis and related with poor prognosis, might contribute to the onset of malignant phenotype [41]. Independently, Hayashi [22] and Mangia [41] envisage a potential role for NHERF1 as a marker in colorectal cancer.…”
Section: Hepatocellular Carcinoma and Colorectal Cancermentioning
confidence: 97%
“…The authors hypothesize that nuclear NHERF1 expression, present in the early stages of carcinogenesis and related with poor prognosis, might contribute to the onset of malignant phenotype [41]. Independently, Hayashi [22] and Mangia [41] envisage a potential role for NHERF1 as a marker in colorectal cancer.…”
Section: Hepatocellular Carcinoma and Colorectal Cancermentioning
confidence: 97%
“…Other studies have showed that NHERF1 is considered a new player in colorectal cancer progression [26]. It has been reported that nuclear NHERF1 expression probably contributes to the malignant phenotype during the early stages of carcinogenesis [27, 28]. Also, cytoplasmic NHERF1 was higher in primary cancer than in adjacent normal mucosa, and tumors overexpressing NHERF1 were associated with nodal and distant metastases, poor grade and lymphovascular invasion (LVI) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi et al [11] observed for the first time alterations of NHERF1 subcellular expression in CRC and have identified it as a new player in CRC progression. Our previous studies showed the expression and sub-localization of NHERF1 in different sites of metastatic CRC, suggesting a dynamic role of this protein in colon carcinogenesis [12, 13]. …”
Section: Introductionmentioning
confidence: 99%